Non‐random patterns of invasion and extinction reduce phylogenetic diversity in island bird assemblages. Issue 2 (13th April 2017) - Baiser, Benjamin; Valle, Dennis; Zelazny, Zoe; Burleigh, J. Gordon
Abstract : Anthropogenically driven changes in bird communities on oceanic islands exemplify the biotic upheaval experienced by island floras and faunas. While the influence of invasions and extinctions on species richness and beta‐diversity of island bird assemblages has been explored, little is known about the impact of these invasions and extinctions on phylogenetic diversity. Here we quantify phylogenetic diversity of island bird assemblages resulting from extinctions alone, invasions alone, and the combination of extinctions and invasions in the historic time period (1500 CE to the current), and compare it to the expected phylogenetic diversity that would result if these processes involved randomly selected island bird species. We assessed phylogenetic diversity and structure at the scale of the island (n = 152), the archipelago containing the islands (n = 22), and the four oceans containing the archipelagos using three measures. We found that extinction, invasion, and the combination of invasion and extinction generally resulted in lower phylogenetic diversity than expected, regardless of the spatial scale examined. We conclude that extinction and invasion of birds on islands are non‐random with respect to phylogeny and that these processes generally leave bird assemblages with lower phylogenetic diversity than we would expect under random invasion or extinction.